Synthesis of N-(5-chloro-6-(quinolin-3-yloxy)pyridin-3-yl) benzenesulfonamide derivatives as non-TZD peroxisome proliferator-activated receptor Î³ (PPARÎ³) agonist - Bajare, S.; Anthony, J.; Nair, A.; Marita, R.; Damre, A.; Patel, Dharmeshkumar; Rao, C.; Sivaramakrishnan, H.; Deka, N. (Elsevier Masson, 2012)
The thiazolidinediones (TZDs) are a class of oral antidiabetic drugs that improve insulin sensitivity in patients with type 2 diabetes. Although the mechanism by which the TZDs lower insulin resistance is unclear, they are known to target the peroxisome proliferator-activated receptor Î³ (PPARÎ³), a nuclear hormone receptor. Ligands for PPARÎ³ regulate adipocyte production and secretion of fatty acids as well as glucose metabolism, resulting in increased insulin sensitivity in adipose tissue, liver, and skeletal muscle. However, TZDs have several adverse effects, including weight gain and liver toxicity. Herein we report identification of non-TZD PPARÎ³ agonists which exhibit beneficial effects similar to that of TZDs in animal models, but without the associated adverse effects. Â© 2012 Elsevier Masson SAS. All rights reserved.